2020
DOI: 10.1590/1413-785220202801227237
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Pelvic Retroversion During Hip Flexion: Evaluation With Accelerometers

Abstract: Objective: To quantify pelvic retroversion during clinical evaluation of hip flexion with accelerometers and to verify the reliability of these sensors to measure hip flexion. Methods: An accelerometer was positioned laterally in the pelvis to measure pelvic retroversion. Another accelerometer was positioned anteriorly on the thigh to evaluate hip flexion amplitude. The evaluations were performed with volunteers in supine position by three raters. For evaluation of pelvic retroversion, the mean ± SD (minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A study that focused on measuring pelvic retroversion during hip flexion used two MPU-6050 IMU sensors connected an Arduino microcontroller that were attached to elastic Velcro-like straps recorded an average angle of 7.30 degrees which is considered reliable for pelvic retroversionwith this result the researchers concluded that the MPU-6050 IMU sensor was considered reliable when performing the ROM Test of hip flexion [11]. The device, however, cannot be considered versatile or scalable.…”
Section: Applications Of the Mpu-6050 Imu Sensor For Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that focused on measuring pelvic retroversion during hip flexion used two MPU-6050 IMU sensors connected an Arduino microcontroller that were attached to elastic Velcro-like straps recorded an average angle of 7.30 degrees which is considered reliable for pelvic retroversionwith this result the researchers concluded that the MPU-6050 IMU sensor was considered reliable when performing the ROM Test of hip flexion [11]. The device, however, cannot be considered versatile or scalable.…”
Section: Applications Of the Mpu-6050 Imu Sensor For Clinicalmentioning
confidence: 99%
“…Previous attempts to develop wearable digital goniometers using sensor technology are neither versatile nor scalable. These studies only considered some of the 34 different ROM tests [6] such as wrist flexion and extension, forearm supination and pronation, radial deviation, and ulnar deviation [7,8]; elbow joint [9 ,10]; hip flexion [11]; and knee flexion and extension [12]. There is no study which attempted to develop a scalable and versatile digital goniometer -one that can support all possible ROM tests in multiple different positions on people with varying heights, weights, and BMI categories.…”
Section: Introductionmentioning
confidence: 99%